2018
DOI: 10.1002/path.5037
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell carcinomas of the ovary and kidney: clarity through genomics

Abstract: Clear cell ovarian carcinoma (CCOC) and clear cell renal cell carcinoma (ccRCC) both feature clear cytoplasm, owing to the accumulation of cytoplasmic glycogen. Genomic studies have demonstrated several mutational similarities between these two diseases, including frequent alterations in the chromatin remodelling SWI-SNF and cellular proliferation phosphoinositide 3-kinase-mammalian target of rapamycin pathways, as well as a shared hypoxia-like mRNA expression signature. Although many targeted treatment option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 173 publications
(193 reference statements)
3
34
0
Order By: Relevance
“…Indeed, CCC has a specific immune‐related molecular profile and epidemiologic associations with ethnicity and endometriosis . Intriguingly, CCC is a major histologic subtype of renal cell carcinoma, with remarkable multifaceted mutational similarities between endometrial and renal CCC . It is reported that loss‐of‐function mutations of PBRM1 , a subunit of the switch‐sucrose nonfermentable (SWI/SNF) chromatin‐remodeling complex, was associated with clinical benefit for ICI in clear‐cell renal carcinoma; this is supported by other reports showing that lower expression of PBRM1 and ARID2 was correlated with higher cytotoxic activity contributed by CD8 T cells in human cancers and that Pbrm1 ‐deficient murine tumor cells were more sensitive to T‐cell‐mediated cytotoxicity .…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, CCC has a specific immune‐related molecular profile and epidemiologic associations with ethnicity and endometriosis . Intriguingly, CCC is a major histologic subtype of renal cell carcinoma, with remarkable multifaceted mutational similarities between endometrial and renal CCC . It is reported that loss‐of‐function mutations of PBRM1 , a subunit of the switch‐sucrose nonfermentable (SWI/SNF) chromatin‐remodeling complex, was associated with clinical benefit for ICI in clear‐cell renal carcinoma; this is supported by other reports showing that lower expression of PBRM1 and ARID2 was correlated with higher cytotoxic activity contributed by CD8 T cells in human cancers and that Pbrm1 ‐deficient murine tumor cells were more sensitive to T‐cell‐mediated cytotoxicity .…”
Section: Discussionmentioning
confidence: 69%
“…As already stated, OCCC is the second most common ovarian cancer after serous carcinoma and represent 26% of ovarian cancer in Southeast Asia [3]. However, fewer molecular targets have been identified for OCCC compared with HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the carcinogenic mechanism and chemoresistance of OCCC are still unclear, several genetic changes have been extensively studied. Compared with HGSOC, OCCC is usually negative for p53 mutations, and the frequency of breast cancer 1 or 2 (BRCA1/2) mutations is low (6.3%) [3,4]. Higher frequencies of AT-rich active domain 1A (ARID1A) and phosphatidylinositol-4,5-diphosphate 3-kinase catalytic subunit alpha (PIK3CA) mutations (36%) have also been observed in OCCC patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As we identified four SNPs and seven associated genes based on the difference of Ov-CCA prevalence by Japanese ancestry, the potential role of seven identified genes in Ov-CCA prognostication or tumorigenesis may be limited to Japanese ancestry. Given that ccRCC has a similar molecular profile to Ov-CCA [28], we performed expression and survival analyses to verify the clinical significance of seven associated genes with the TCGA-ccRCC dataset composed of various ancestries. In addition, further validation was conducted in a minority ancestry with our Korean EOC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…gov/tcga/tcgaHome2.jsp). As there were no Ov-CCA cases in the TCGA database, a clear cell renal cell carcinoma (TCGA-ccRCC) dataset, reported to have similar molecular profiles to that of Ov-CCA, was included in the survival analysis as an alternative [28]. In addition, the HGSOC dataset was included as a control.…”
Section: Analysis Of the Clinical Significance Of The Seven Identifiementioning
confidence: 99%